Pendidikan Tanpa Kekerasan Dalam Perspektif Pendidikan Islam Menurut Drs. Abd. Rahman Assegaf, M.A - Nafi'ah, Khoirul; Amirudin, noor; Ladamay, Man Arfa' (Jurnal Mahasiswa Pendidikan, 2021)
As for studying violence in education, a qualitative research method is used (Library Research) from ABD's books. Rahman Assegaf entitled Education without Violence Typology of Conditions, Cases, and Concepts as well as being a primary data source and for secondary data sources taking from previous research such as journals, theses. The analysis technique used is descriptive data analysis and the data collection method uses the documentation method. Violence cannot be solved by violence, because it will lead to new violence. Of the several cases that emerged after the conditions, factors and triggers of violence were known, there was a concrete solution that had to be taken, namely preventive/preventive steps to minimize acts of violence. Peace education is a concept of education that is non-violent because it contains religious values ​​(Islam) because Islam is peace that guides humans to uphold human rights and behave socially by humanizing humans (Humanism).